Effects of strong bite force on the facial vertical dimension of pembarong performers - C. Christina; Achmad Sjafei; Ida Bagus Narmada (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: A pembarong performer is a reog dancer who bites on a piece of wood inserted into his/her mouth in order to support a 60 kg Barongan or Dadak Merak mask. The teeth supporting this large and heavy mask are directly affected, as the strong bite force exerted during a dance could affect their vertical and sagital facial dimensions. Purpose: This study aimed to examine the influence of the bite force of pembarong performers due to their vertical and sagital facial dimensions. Methods: The study reported here involved fifteen pembarong performers and thirteen individuals with normal occlusion (with specific criteria). The bite force of these subjects was measured with a dental prescale sensor during its centric occlusion. A cephalometric variation measurement was subsequently performed on all subjects with its effects on their vertical and sagital facial dimensions being measured. Results: The bite force value of the pembarong performers was 394.3816 ± 7.68787 Newtons, while the normal occlusion was 371.7784 ± 4.77791 Newtons. There was no correlation between the bite force and the facial sagital dimension of these subjects. However, a significant correlation did exist between bite force and lower facial height/total facial height (LFH/TFH) ratio (p = 0.013). Conversely, no significant correlation between bite force and posterior facial height/total facial height (PFH/TFH) ratio (p = 0.785) was detected. There was an inverse correlation between bite force and LFH/TFH ratio (r = -.464). Conclusion: Bite force is directly related to the decrease in LFH/TFH ratio. Occlusal pressure exerted by the posterior teeth on the alveolar bone may increase bone density at the endosteal surface of cortical bone.